Evaluation of West Nile Virus Diagnostic Capacities in Veterinary Laboratories of the Mediterranean and Black Sea Regions - Pérez-Ramírez, Elisa; Cano-Gómez, Cristina; Llorente, Francisco; Vodica, Ani; Veljović, Ljubiša; Toklikishvilli, Natela; Sherifi, Kurtesh; Sghaier, Soufien; Omani, Amel; Kustura, Aida; Krstevski, Kiril; Karayel-Hacioglu, Ilke; et al. (MDPI AG, 2020)
The increasing incidence of West Nile virus (WNV) in the Euro-Mediterranean area warrants the implementation of effective surveillance programs in animals. A crucial step in the fight against the disease is the evaluation of the capacity of the veterinary labs to accurately detect the infection in animal populations. In this context, the animal virology network of the MediLabSecure project organized an external quality assessment (EQA) to evaluate the WNV molecular and serological diagnostic capacities of beneficiary veterinary labs. Laboratories from 17 Mediterranean and Black Sea countries participated. The results of the triplex real time RT-PCR for simultaneous detection and differentiation of WNV lineage 1 (L1), lineage 2 (L2) and Usutu virus (USUV) were highly satisfactory, especially for L1 and L2, with detection rates of 97.9% and 100%, respectively. For USUV, 75% of the labs reported correct results. More limitations were observed for the generic detection of flaviviruses using conventional reverse-transcription polymerase chain reaction (RT-PCR), since only 46.1% reported correct results in the whole panel. As regards the serological panel, the results were excellent for the generic detection of WNV antibodies. More variability was observed for the specific detection of IgM antibodies with a higher percentage of incorrect results mainly in samples with low titers. This EQA provides a good overview of the WNV (and USUV) diagnostic performance of the involved veterinary labs and demonstrates that the implemented training program was successful in upgrading their diagnostic capacities.
Keywords: West Nile Virus; external quality assessment; MediLabSecure